Support Strategy for Executive Function in Children of Low-Income Families: The Marshmallow Test Has a Learning Value - Watanabe, Nobuki (Frontiers in Education, 2022)
Executive function (EF) development is an important part of infancy and childhood, promoting success in later life. It is desirable to develop targeted methods to enable EF. There is an urgent need for easily-implemented proposals to ameliorate educational disparities between income groups. EF is a skill its possessor can use to inhibit thoughts and emotions. There is a relationship between EF and the prefrontal cortex. The Wechsler Intelligence Scale for Children’s (WISC-IV) Working Memory Index (WMI) test for thinking and the marshmallow test for emotions have been used to measure EF, but these tests themselves carry a load of inhibitions. Therefore, we can assume a natural value in learning to improve on the test. The marshmallow test does not require parental expertise in preparation or implementation, and it entails little financial burden. If the is a potential value in learning how to do better on the test, it will be easy for parents in low-income families to help their children improve. I examined whether the marshmallow test itself can support EF. Measurements of brain activity in the prefrontal cortex over eight days showed that children who took the marshmallow test during this time were more active than those who took the WMI test or the abacus test. In addition, brain activity stabilizes or declines after completing a task. Therefore, the results suggest that continued use of the marshmallow test can support EF even in low-income families.